Some Coincidence and Common Fixed-Point Results on Cone b2-Metric Spaces over Banach Algebras with Applications to the Infinite System of Integral Equations. (3rd September 2021) - Islam, Ziaul; Sarwar, Muhammad; Filali, Doaa; Jarad, Fahd
Abstract : In this article, common fixed-point theorems for self-mappings under different types of generalized contractions in the context of the cone b 2 -metric space over the Banach algebra are discussed. The existence results obtained strengthen the ones mentioned previously in the literature. An example and an application to the infinite system of integral equations are also presented to validate the main results.